A 3-Week, Open Label Study to Evaluate the Efficacy and Safety of Extended Release Quetiapine Fumarate in the Treatment of Agitation in Patients with Schizophrenia - Koh, Ong Hui; Sulaiman, Ahmad Hatim; Gill, Jesjeet Singh; Pillai, Subash Kumar; Jambunathan, Stephan Thevananthan; Rashid, Rusdi Abdul (Taylor & Francis, 2013)
Objective: To evaluate the efficacy of extended-release quetiapine fumarate (XR) monotherapy once daily, in the treatment of patients with acute episodes of schizophrenia and agitation. Method: Our study was a 3-week open-label study conducted in adult in- or outpatients with schizophrenia. Quetiapine XR was initiated at 300 mg on day 1, 600mg on day 2, and 400-800 mg (at the investigator’s discretion) on day 3 and onwards. The primary endpoint was the change from baseline in the Positive and Negative Syndrome Scale Excited Component (PANSSEC) score. Secondary endpoints included change from baseline in PANSS-Positive, PANSS-Negative, PANSSGeneral Psychopathological (PANSS-G) subscale scores, total PANSS score, PANSS aggression, hostility and depression cluster scores, CGI-Severity of illness (CGIS) and the absolute CGI-Improvement (CGI-I) scales. Tolerability was assessed based on reported adverse events (AEs), the Simpson-Angus Scale (SAS) and Barnes Akathisia Rating Scale (BARS) scores, laboratory measurements and electrocardiograms (ECGs). Results: Of 40 patients enrolled, 35 completed the study. At day 21, statistically significant improvements versus baseline were seen for the primary and all secondary endpoints assessed. The incidence of AEs was low, and all were mild to moderate in severity. No extrapyramidal symptoms (EPS) as measured by the SAS and BARS were reported, indicating that the treatment was well tolerated. Hospitalization was required in one out-patient due to a relapse of psychosis, but was not considered to be treatment related. Conclusion: Once-daily quetiapine fumarate XR (400- 800 mg/day) was effective in reducing agitation and a broad range of symptoms in acute schizophrenia. Treatment, including rapid dose escalation, was generally well tolerated in this study.